Effects of leachate-based liquid organic fertilizer on soil fertility and chili growth in biochar-amended marginal soil - Alim, Nurmaranti; Sanjaya, Muhammad Fahyu; Ramadan, Laode Muhammad Asdiq Hamsin; Roland, Dicky; Irwansyah, Irwansyah; Fitri, Fitri (Jurnal Ilmiah Pertanian, 2025)
Soil fertility degradation and limited access to sustainable inputs pose major constraints in marginal agricultural lands. Organic waste leachate, although rich in nutrients, often contains phytotoxic compounds that limit its direct application as fertilizer. This study evaluated the effect of leachate-based liquid organic fertilizer (LOF) on soil fertility and the growth response of chili pepper (Capsicum frutescens) in marginal soils amended with biochar. Four treatments were tested: no LOF, 20% LOF, 40% LOF, and 60% LOF. Soil analysis showed that LOF application improved pH, organic carbon, and macronutrient content (N, P,K), with the highest pH in the 20% LOF treatment and the highest C-organic in the 60% LOF treatment. However, the best plant growth was observed in the control treatment, possibly indicating inhibitory effects of phytotoxic compounds such as phenols and organic acids present in the LOF. Although 20% LOF resulted in the highest fruit weight, differences among treatments were not statistically significant. These results suggest that while leachate-based LOF enhances soil quality, its high concentration may hinder plant growth. The findings support the potential use of leachate as a low-cost nutrient source for sustainable agriculture, provided that proper detoxification and formulation strategies are applied.